Effect of Methanolic Extract of Ficus trigonata Leaves on Lipid Profile and Liver Function Indices in Plasmodium berghei Infected Mice (CaJoST, 2024)
The research was designed to evaluate the effect of methanolic extract ofFicus trigonata leaves on lipid profile and liver function indices inPlasmodium berghei infected mice. The extract was prepared by macerationand tested for antioxidant activity using Diphenyl-picryl hydrazyl (DPPH) andFerric Reducing Antioxidant Power (FRAP) assays. Thirty-six (36) mice wereused for the study. The extract was administered orally at doses of 100, 200and 300 mg/kg to infected mice for four days and compared to standarddrug chloroquine and normal saline controls. Lipid profile and liver functionindices were determined using standard methods. The results showed thatthe extract exhibited concentration-dependent antioxidant activity in bothDPPH and FRAP assays, with an IC50 values of 0.49 and 0.37 mg/mL,respectively. The elevated levels of Triglycerides and Total cholesterol weresignificantly (P